Near‐infrared spectroscopy for examination of prefrontal activation during cognitive tasks in patients with major depressive disorder: A meta‐analysis of observational studies. Issue 1 (29th July 2014) - Zhang, Huijun; Dong, Wentian; Dang, Weimin; Quan, Wenxiang; Tian, Ju; Chen, Ru; Zhan, Siyan; Yu, Xin
<x xml:space="preserve">Abstract</x> Aims Near‐infrared spectroscopy has the potential for aiding the diagnosis of major depressive disorder. The purpose of this study was to systematically review the evidence from observational studies regarding the use of near‐infrared spectroscopy in patients with major depressive disorder and to identify the characteristic pattern of prefrontal lobe activity in major depressive disorder. Methods medline, PubMed, Cochrane Library and Web of Science databases were searched in December 2013. All case–control studies were included. The quality of evidence was examined using the Newcastle–Ottawa Quality Assessment Scale. The primary outcome measures were the mean oxygenated and deoxygenated hemoglobin alterations of the cerebral cortex during cognitive activation periods. The standard mean difference for the overall pooled effects across the included studies was estimated using random or fixed effect models. The primary outcome measures were included in the meta‐analysis. Results Fourteen studies met the inclusion criteria. Six studies (n = 692 participants) were included in the analysis of the mean oxygenated hemoglobin alterations; the pooled mean standardized difference was −0.74 (95% confidence interval, −0.97 to −0.52), indicating that patients with major depressive disorder were associated with attenuated increase in oxygenated hemoglobin during cognitive activation in the prefrontal regions compared to healthy controls. Five studies (n = 668 participants) were included in the analysis of mean deoxygenated‐hemoglobin changes; the pooled standardized mean difference was 0.18 (95% confidence interval, −0.20 to 0.56). Conclusions Using near‐infrared spectroscopy measurements, we observed that compared to healthy subjects, patients with major depressive disorder had significantly lower prefrontal activation during cognitive tasks.